PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI PT. FIF GROUP CABANG UJUNG BATU POS BANGUN JAYA - Dzikra, Faira Medina (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This research was conducted at PT FIF Ujung Batu Branch Group Pos Bangun Jaya. This research aimed to know The effect of leadership on employee performance at PT FIF Ujung Batu Branch Group Pos Bangun Jaya. The population in this study is all empoyee’s totaling 30 people. The sampling technique in this study used the sampling census method. Data analysis used in this study uses quantitative descriptive method. Based on the results of data processing carried out from the results of hypothesis testing with the t test obtained tcount (3.402) greater than the value of t table (1.699), with a significant level of 0.02 <0.05, it can be concluded that Ho is rejected and Ha is accepted, which means leadership has a significant effect of employee performance at PT FIF Ujung Batu Branch Group Pos Bangun Jaya. For the coefficient of determination (R2) the value of determination coefficient (R2) of 0.523 means that the contribution or contribution of independent variable to the dependent variable is 0.292 or 29,2% while the remaining 70,8% is influenced by other variables that are ignored or not examined